Smallholder farmers' understandings of and responses to climate change in Malawi: a case study of Mphunga group village, Salima district - Saruchera, Munyaradzi Matthew (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.